From techno talk to social reflection - van Est, Rinie (Ökologisches Wirtschaften - Fachzeitschrift, 2010)
In politics many things depend on how an issue is framed from different points of view, including science and technology, society and public engagement. This threefold-framing of converging technologies has shaped the political and public debate on the topic. What are the lessons for the role of public participation in the field of converging technologies?
Keywords: science; technology; public engagement; converging technologies; public participation